Socio-Emotional Development Among Adolescents Raised in Families With or Without Grandparents in Dharan, Nepal: A Comparative Study (MedS Alliance Journal of Medicine and Medical Sciences, 2023)
Introduction: Socio-emotional development can be defined by convergence of social and emotional growth. Adolescence, transitional phase of growth and development between childhood and adulthood. Grandparents are often highly involved as secondary caregivers for their grandchildren and may influence children’s psychological and physical health outcomes.Materials and Methods: A comparative cross- sessional study was conducted in a Dharan 17 and samples were selected using the purposive sampling method. A total of 156 adolescents (78 in each group) with an age range of 15 to 17 years were interviewed using the self- rated version of Strength and Difficulty Questionnaire (SDQ) .Data was analyzed using SPSS version 11.6. Questions were in the Likert scale 0 (not true), 1 (somewhat true) and 2 (certainly true). Descriptive statistics were used to describe socio-demographic data. Pearson Chi-square test was used to compare the socio-emotional development among adolescents raised in families with or without grandparents and to find out the association between dependent and independent variables.Results: Pearson chi-square depicts significant difference in socio-emotional development raised in families with or without grandparents in Dharan 17 (p- value